System to improve the thermal efficiency of steam generators, through energy recovery from purges - Huapaya Barrientos, José (2003)
This paper focuses on the best use of energetic resources on industrial activity, according to the international and national need of competitiveness. Annually, a quantification of fuel savings is made and the economic benefit accomplished by the companies is checked. This was realized through the energy recovered from the elimination process occured the operation of a steam generator. A real case is discussed to convalidate the stated concepts